On delay robustness improvement using digital Smith predictor for networked control systems - Bonala S.; Subudhi B.; Ghosh S. (My University, 2025)
This paper presents a study on delay robustness improvement ability of a digital Smith predictor based delay compensator for networked control systems with bounded network induced time-varying delays and packet losses. The compensator is considered to be implemented in digital form with time-driven controller and event-driven actuator configuration. The uncertain system model is represented in polytopic form and Lyapunov method is used for stability analysis in terms of linear matrix inequalities. The performance of the digital predictor in terms of delay-tolerability is then tested on two numerical examples and verified with simulation using TrueTime simulator. It is found that the selection of predictor delay can be made based on bounds of network delays to improve the performance of the controller. © 2017 European Control Association